2013
DOI: 10.1016/j.mjafi.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A survey of attitude of frontline clinicians and nurses towards adverse events

Abstract: Medical errorAdverse events a b s t r a c t Background: It is often said that doctors are only human. However, technological wonders, apparent precision of diagnostic tests and scientific innovation have created an expectation of perfection from medical science. Patient safety and prevalence of adverse events on the hospital floor have become issues of serious concern for the healthcare environment.Method: The study had cross-sectional design, done over a period of one year at a teaching medical college and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
3
7
0
1
Order By: Relevance
“…The second most frequent category was related to routines and guidelines that were not followed by health care professionals. This finding is in line with findings reported by Chakravarty (2013), which showed that errors were built into existing routines and devices, which was the case in incidents in the operating room reported in this study. It is a challenge to enhance patients' safety and evidence-based care.…”
Section: Discussionsupporting
confidence: 94%
“…The second most frequent category was related to routines and guidelines that were not followed by health care professionals. This finding is in line with findings reported by Chakravarty (2013), which showed that errors were built into existing routines and devices, which was the case in incidents in the operating room reported in this study. It is a challenge to enhance patients' safety and evidence-based care.…”
Section: Discussionsupporting
confidence: 94%
“…Assessments from a similar study demonstrate the results were similar to the recent study, in which the "Teamwork within unit" has allocated the highest score among the patient safety culture dimensions (24).Regarding errors, researches showed that if employees do not interact with each other about the errors occurring in the department and hide the errors, the individuals will not be aware of the errors and able to provide a solution to prevent re-occurring of the errors, consequently, operational program of the staff will not change (25).In examining the viewpoints of the samples concerning the phrases of the safety culture questionnaire in the dimension of, "teamwork within units", the highest mean in the terms ranking was related to the term, "In this unit, people treated each other with respect". Mutual respect is one of the most substantial factors that affect the performance of the hospital departments.…”
Section: Discussionsupporting
confidence: 81%
“…17 The relevance of engaging the professionals who have direct contact with the patient in this safety improvement process should be highlighted, motivating them to feel safe to do so, admitting human fallibility and the need to reconsider the healthcare processes and routines. 13 …”
mentioning
confidence: 99%